600 essential words for the TOEIC test : test of English for international communication - Lougheed, Lin, Dr. (Nxb. Trẻ, 2011)
General business; Office issues; Personnel; Purchasing; Financing and budgeting; Management issues; Restaurants and events; Travel; Entertainment; Health.